2019
DOI: 10.1038/s41598-019-44033-5
|View full text |Cite
|
Sign up to set email alerts
|

A sulfur and nitrogen cycle informed model to simulate nitrate treatment of reservoir souring

Abstract: Nitrate treatment has been widely used in various seawater injection projects to treat biologic sulfate reduction or reservoir souring. To design a promising nitrate treatment plan, it is essential to have a comprehensive understanding of reactions that represent the microbial communities of the reservoir and mechanisms through which the souring process is inhibited. We employ a new approach of evaluating different reaction pathways to design reaction models that reflect governing microbial processes in a set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…Moreover, An et al (2017) and Marietou et al (2020) confirmed that nitrite inhibition is the most effective nitrate‐based souring mitigation mechanism. The SOB distributions of samples collected from oil fields were affected by the levels of nitrate and nitrite, which could stimulate the growth of NR‐SOB (Greene et al, 2003; Hubert et al, 2005; Jahanbani Veshareh & Nick, 2019; Qi et al, 2022). In addition, the concentration of acetate had an obvious influence on the SOB communities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, An et al (2017) and Marietou et al (2020) confirmed that nitrite inhibition is the most effective nitrate‐based souring mitigation mechanism. The SOB distributions of samples collected from oil fields were affected by the levels of nitrate and nitrite, which could stimulate the growth of NR‐SOB (Greene et al, 2003; Hubert et al, 2005; Jahanbani Veshareh & Nick, 2019; Qi et al, 2022). In addition, the concentration of acetate had an obvious influence on the SOB communities.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid hydrogen sulphide formation in oil fields, the injection of oxygen-containing nitrate solutions is a widely used measure for the petroleum industry to stimulate NRB to compete with SRB for degradable organics in oil, oxidise hydrogen sulphide to sulphur or sulphate, and suppress sulphate reduction by nitrite or by the higher redox potential that is created by nitrate and oxygen injection (Bødtker et al, 2008;Hubert & Voordouw, 2007;Jurelevicius et al, 2020;Kaster et al, 2007;Marietou et al, 2020;Qi et al, 2022;Voordouw et al, 2009). Studies have also shown that many sulphur-oxidising bacteria (SOB), which can catalyse sulphide oxidation coupled with nitrate reduction, are stimulated by nitrate (Aoyagi et al, 2021;Hubert & Voordouw, 2007;Jahanbani Veshareh & Nick, 2019;Qi et al, 2022). As reservoir environments contain numerous reduced sulphur compounds (e.g., thiosulphate, sulphide and ferrous sulphide and elemental sulphur), SOB, including Thiobacillus, Sulfurospirillum, Sulfuricurvum, Sulfurovum and Sulfurimonas, are commonly detected in reservoir environments (Gao et al, 2015(Gao et al, , 2022Gao & Fan, 2023;Hubbard et al, 2014;Tian et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been found that adding nitrite to injection water is more effective than other treatment chemicals in oilfields, including in high-temperature scenarios [ 49 ]. Modeling simulations based on several case studies asserted that nitrite is the main inhibitory chemical in nitrate-treated sour oilfield systems [ 50 ]. In the present study, the produced fluid samples were from a high-temperature reservoir that can reach temperatures of up to 90 °C.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the produced fluid samples were from a high-temperature reservoir that can reach temperatures of up to 90 °C. The mode of action of nitrite in sulfate reduction inhibition, in addition to its efficacy in high-temperature oil fields, may be the reason that nitrite performed better across both platform samples for reducing sulfate reduction, as opposed to the variability in efficacy of the nitrate treatments [ 23 , 24 , 50 ]. The corrosion rates (assessed after the 156-day incubation) measured for the nitrite-treated microcosms in our study indicate a low corrosion risk ( Figure 6 ), however the potential chemical corrosivity of nitrite can be observed in the nitrite-treated sterile controls that showed a moderate corrosion rate of 0.07 mm/year [ 27 ].…”
Section: Discussionmentioning
confidence: 99%